(3KeGQ ebGdI CQSWhWGdjS aj JOHjQ GdefRds - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3GdaQb Hjf GdSjGSI GdefRdjI hGdSjGSjI GdeOfjI eeGKd ddaQb Hjf GdefRd hGdeOjfI s
(3BNQgG (B:s
(3hjNJGQ CUdM GdChGfi hCHbGgG Ydi GdESJYeGd hjchf cd Ufa efgG eYdhe GdehVY MJi dGjJWdH YfO GdMGLI JeJ GdKeQI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/11) s
Keywords: (3GdadSaI hGdefWbs